The effects of the addition of banana peels and coconut water on the increasing nutrition of biofertilizer from rice washing water - Wika Atro Auriyani; D. Deviany; Latasya Adelia Wulandari; Yosia Abdi Cahyono; Desi Riana Saputri; Yunita Fahni, Reni Yuniarti; Andri Sanjaya; D. Damayanti; Fauzi Yusupandi; Rifqi Sufra; Misbahudin Alhanif (Jurnal Teknik Kimia, 2024)
Indonesia is reducing the use of chemical fertilizers for sustainable cultivation of agricultural land, so the use of biological fertilizers needs to be increased. One source of biological fertilizers is rice washing water waste. This research aims to determine the effect of adding banana peel and coconut water to the nutritional content of rice washing water biofertilizer, knowing the right fermentation time, and knowing the content of primary macro nutrients (N, P, K) in the biological fertilizer of fermented rice washing water. In this study there were 2 groups of fertilizers, namely group 1 (7 days anaerobic fermentation) and group 2 (14 days anaerobic fermentation), there were also groups A (rice washing water + banana peel + MOL), B (rice washing water + coconut water + MOL), and C (rice washing water + banana peel + coconut water + MOL). At the end of the research, it will be known that the addition of banana peel and coconut water can increase the organic C, N, P and K content of the biofertilizer in rice washing water. Biofertilizer applied to mustard plants, the 1B fertilizer group showed better yields than the commercial liquid organic fertilizers by increasing the height of the mustard plant up to 17.9 cm for 30 DAP with the primary macro nutient contents in the 1B fertilizer respectively 0.05 % N; 0.03 % P; 0.18 % K.